The Role of Competence on Performance Leadership Style as an Intervening Variable - Djoko Soelistya; Ade Septiarisna Warindra; Eva Desembrianita; Titik Purwanti; Suhardi Suhardi (Jurnal Manajemen Industri dan Logistik, 2024)
This study aims to analyze the effect of employee competence on their performance in the company through the leadership style in the company, while the following research uses a quantitative method that uses a population of employees of the Plastic Woven Packaging Manufacturing Company using a sample of the production department of 100 respondents. The following research results show that the influence of (1) employee competence has a significant influence on performance, (2) employee competence has a significant influence on leadership style, (3) leadership style has a significant influence on performance, while profit sharing has an indirect effect through the mediating variable style (4) Competence has a significant direct effect in order to provide an increase in employee performance even though it is not through Leadership Style as a mediating variable. The company should pay attention and provide an increase in the competence that can affect employee performance.